Pengaruh Metode Gamifikasi Terhadap Hasil Belajar Mahasiswa Pada Mata Kuliah Anguttara Nikaya di STABN Sriwijaya - Rusmiyati (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2025)
The Anguttara Nikaya course is a compulsory subject in the Buddhist Religious Education Study Program. Students often struggle to understand sutta texts due to their metaphorical language and repetitive narrative structure. This study aims to measure the effectiveness of the gamification method in improving student learning outcomes. The research employs a quantitative approach using a Single Subject Research (SSR) design with the Applied Behavior Analysis (A-B-A) type. The results indicate that in the initial baseline phase (A1), students had a low understanding of sutta. After implementing the gamification method during the intervention phase (B), there was a significant improvement in comprehension and learning motivation. In the final baseline phase (A2), student performance remained stable and nearly matched the intervention phase. The gamification method has proven to be an effective tool in enhancing student learning outcomes and can be applied as an interactive learning approach in Buddhist studies.